Strategies in Education Christian Morals for Children with Intellectual Disabilities A Guide for Parents - Magdalena, Emy; Tari, Ezra (Jayapangus Press, 2024)
Christian moral education strategies for children with intellectual disabilities play an important role in the formation of solid character and spiritual values. This guide is designed to assist parents in effectively implementing the principles of Christian moral education at home. The main focus of these strategies is on developing a loving environment, a deep understanding of the child's special needs, and the use of creative and adaptive learning methods. Parents are encouraged to incorporate Bible stories, prayer, and other spiritual activities in the child's daily routine. In addition, the importance of parental example in applying Christian values is also emphasized, as children tend to learn through observation and imitation. Involving children in church communities and social activities can help them feel a sense of community and strengthen their sense of spiritual identity. An emphasis on patience, understanding, and emotional support is essential in dealing with the challenges that arise in this moral education process. The guide also includes practical tips for dealing with difficult behavior, as well as ways to motivate children to continue learning and growing in their Christian faith. With a loving and inclusive approach, it is hoped that children with intellectual disabilities can develop strong Christian morals and grow into individuals of integrity and faith. This guide aims to provide comprehensive support and guidance for parents, so that they can be effective primary educators of their children on their spiritual and moral journey.